(untitled) (Pedagogy of Higher and Secondary Education, 2006)
In article some elements of process offormation of aesthetic concepts at lessons of an aesthetics at school are examined: problems in development by aesthetic terminology by pupils of school law and criterion of an estimation of knowledge value of inlersubject connections. problems tasks of the teacher at the certain stages; historical revonstniction concept form" on V. Tatarkevichu is sent.